How Digital Transformation Can Affect Product Innovation Performance MSMEs: Evidence from West Java - Manalu, Vigory Gloriman; Adzimatinur, Fauziyah (Jurnal Aplikasi Manajemen, 2024)
This study aims to examine the relationship of foresight capability to the innovation performance of SMEs by using digital transformation as a mediating variable. This study uses a quantitative research method. Data collection was carried out through a structured offline questionnaire. The technique of determining the sampling is done by using purposive sampling. The population in this study were SMEs originating from the West Java region, with a total of 187 questionnaires collected. This research uses structural equation modeling (SEM) to test the hypothesis. This study proposes ten hypotheses, of which seven direct effect hypotheses and three hypotheses test the mediating effect. The study's results found that foresight capability can affect product innovation performance. The effect of foresight capability (network and analysis) can affect digital transformation, but the time horizon cannot affect digital transformation. Digital transformation can affect the performance of MSMEs product innovation. This study found that digital transformation can partially mediate network relationships and analysis on product innovation performance and cannot mediate time horizon relationships on product innovation performance. The findings of this study enrich the foresight literature, digital transformation, and innovation performance of MSMEs products.